The Construction of women in Women's magazine fiction a feminist stylistic approach - Gatan, Emma Honeylette R. (College of Arts and Letters, University of the Philippines Diliman, 2001)
This study tries to determine how women are constructed through language in women's magazine fiction. It aims to discover how language is used and manipulated to arrive at these constructs. The chosen texts consist of seventeen short stories, bearing the theme of romance, published in the year 2000 issues of MOD magazine. The texts are analyzed using the principles of feminist stylistics. This method of analysis examines the text at three levels: the word, phrase or sentence, and then finally, discourse. Results show that there are indeed differences between the way men and women are presented in the texts. In general, the texts project women as being concerned with emotion rather than action, women who are subordinates rather than co-equals of men, and women who are taken as fragmented body parts rather than as one conscious being.